Analisis Visual Dalam Fotografi Sejarah Kemerdekaan Indonesia Karya Alex dan Frans Mendur - Martinus Eko Prasetyo Kaparang; William Sanjaya (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
Photojournalism can depict events that hold meaning. In Indonesia, the inception of photojournalism was led by Alex Mendur and Frans Mendur. Alex and Frans Mendur were photojournalists who captured images of events during the periods of independence, the New Order era, and the Reform era. Besides documenting these events, they also photographed the atmosphere and ordinary people after the independence period. This research aims to understand the role of composition in the photographic works of Alex and Frans Mendur and the extent to which composition was applied. To prove and understand this, the research is necessary. The theory used in this study is the photography composition theory proposed by Budhi Santoso. The research method employed is qualitative descriptive, utilizing the theories of Budhi Santoso and Paul Hill as analytical tools. Based on the analysis conducted, it is concluded that the photographic works of Alex and Frans Mendur employ various compositions. These compositions are used to guide the viewer's focus on specific parts of the image. Furthermore, these compositions highlight subjects such as heroic figures and landscapes, creating an impact within the images. This research is expected to serve as a reference in the field of basic journalistic photography, emphasizing the importance of applying visual composition in capturing a narrative moment, making it easier for the audience to understand and interpret the visual message being conveyed, a practice that dates back to the period of Indonesian Independence.